2006
DOI: 10.1128/jb.188.10.3631-3644.2006
|View full text |Cite
|
Sign up to set email alerts
|

The Ornibactin Biosynthesis and Transport Genes of Burkholderia cenocepacia Are Regulated by an Extracytoplasmic Function σ Factor Which Is a Part of the Fur Regulon

Abstract: Burkholderia cenocepacia mutants that fail to produce the siderophore ornibactin were obtained following mutagenesis with mini-Tn5Tp. These mutants were shown to be growth restricted under conditions of iron depletion. In eight of the mutants, the transposon had integrated into one of two genes, orbI and orbJ, encoding nonribosomal peptide synthetases. In the other mutant, the transposon had inserted into an open reading frame, orbS, located upstream from orbI. The polypeptide product of orbS exhibits a high d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
123
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 80 publications
(130 citation statements)
references
References 83 publications
5
123
0
2
Order By: Relevance
“…There are three known species of this linear hydroxamate siderophore: ornibactin-C4, ornibactin-C6 and ornibactin-C8 produced by Bcc strains (Stephan et al, 1993), and ferrated ornibactin is transported across the outer membrane by a ferric-ornibactin receptor, OrbA. Similar to Pseudomonas siderophore biosynthesis, the ornibactin operon is Fur regulated (Agnoli et al, 2006). The second siderophore produced by some strains of the Bcc is pyochelin (Sokol, 1986), and the production of ornibactin and pyochelin correlates with morbidity and mortality in CF (Sokol, 1986;Visser et al, 2004).…”
Section: Siderophore-mediated Iron Acquisitionmentioning
confidence: 99%
“…There are three known species of this linear hydroxamate siderophore: ornibactin-C4, ornibactin-C6 and ornibactin-C8 produced by Bcc strains (Stephan et al, 1993), and ferrated ornibactin is transported across the outer membrane by a ferric-ornibactin receptor, OrbA. Similar to Pseudomonas siderophore biosynthesis, the ornibactin operon is Fur regulated (Agnoli et al, 2006). The second siderophore produced by some strains of the Bcc is pyochelin (Sokol, 1986), and the production of ornibactin and pyochelin correlates with morbidity and mortality in CF (Sokol, 1986;Visser et al, 2004).…”
Section: Siderophore-mediated Iron Acquisitionmentioning
confidence: 99%
“…Most clinical isolates of B. cenocepacia produce the siderophores ornibactin and pyochelin (Sokol, 1986;Visca et al, 1993;Meyer et al, 1995;Darling et al, 1998;Thomas, 2007), and their production has been correlated with morbidity and mortality in CF patients and/or shown to contribute to pathology in animal models of respiratory infection (Sokol, 1986;Sokol & Woods, 1988;Sokol et al, 1999Sokol et al, , 2000Visser et al, 2004;Uehlinger et al, 2009). Ornibactin contains an L-ornithine-D-hydroxyaspartate-L-serine-L-ornithine backbone that requires two non-ribosomal peptide synthetases (NRPSs), OrbI and OrbJ, for its assembly (Stephan et al, 1993;Agnoli et al, 2006). The yellow-green fluorescent siderophore pyochelin is biosynthesized from salicylate by the successive addition and cyclization of two molecules of cysteine (Ankenbauer et al, 1988;Reimmann et al, 1998;Quadri et al, 1999;Quadri, 2000;Crosa & Walsh, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…This enzyme transfers the P-pant moiety from coenzyme A (CoASH) to an invariant serine residue in the conserved phosphopantetheinylation site [FFxLGG(D/H)S(L/I)] of the PCP/ArCP domain Marahiel et al, 1997;Quadri et al, 1998b). A total of four predicted PCP domains are present in the ornibactin biosynthetic machinery (three in OrbI and one in OrbJ), each of which binds one of the four amino acid building blocks, and three PCP/ArCP domains occur in the NRPSs involved in pyochelin biosynthesis (two in PchE and one in PchF) (Quadri, 2000;Agnoli et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our analysis revealed that all six strains encode biosynthesis clusters which resemble ornibactin (Fig. 4E), a siderophore synthesis cluster of Burkholderia cenocepacia (Agnoli et al, 2006). Siderophore production was confirmed for all the six Collimonas strains, albeit with different production efficiency (Fig.…”
Section: Iron Acquisitionmentioning
confidence: 72%